2017
DOI: 10.1021/acsami.7b04235
|View full text |Cite
|
Sign up to set email alerts
|

High-Performance Zinc Tin Oxide Semiconductor Grown by Atmospheric-Pressure Mist-CVD and the Associated Thin-Film Transistor Properties

Abstract: Zinc tin oxide (Zn-Sn-O, or ZTO) semiconductor layers were synthesized based on solution processes, of which one type involves the conventional spin coating method and the other is grown by mist chemical vapor deposition (mist-CVD). Liquid precursor solutions are used in each case, with tin chloride and zinc chloride (1:1) as solutes in solvent mixtures of acetone and deionized water. Mist-CVD ZTO films are mostly polycrystalline, while those synthesized by spin-coating are amorphous. Thin-film transistors bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…35,36 This approach has also been used by a number of other teams. [37][38][39][40] The advantage of this approach is its versatility: the DTC forms complexes with a large number of different metals 41 which have similar decomposition temperatures. This enables obtaining single and multicomponent films of different compositions with different levels of doping with the specified components 42,43 while using one basic organic ligand (DTC).…”
Section: Introductionmentioning
confidence: 99%
“…35,36 This approach has also been used by a number of other teams. [37][38][39][40] The advantage of this approach is its versatility: the DTC forms complexes with a large number of different metals 41 which have similar decomposition temperatures. This enables obtaining single and multicomponent films of different compositions with different levels of doping with the specified components 42,43 while using one basic organic ligand (DTC).…”
Section: Introductionmentioning
confidence: 99%
“…However, due to environmental risks associated with using toxic cadmium (Cd) and it's relatively low band gap (2.4 eV) [1], many research efforts were focused on the replacement of CdS with new Cd-free materials that fulfill the requirements for a non-toxic and effective buffer layer [2]. Recently, a class of thin-film metal oxide semiconductors characterized by high optical transparency and a good electrical conductivity had been applied in several optoelectronic fields: thin film transistors (TFT) [3], gas sensors [4] and buffer layers in many solar cells, such as CIGS (18.2%) [5], CZTS (12.6%) [6] and CZTSSe (8.6%) [7]. Known as one of the transparent conductive oxides (TCOs) (Zn,Sn)O or ZTO had demonstrated its ability to be a promising alternative as a buffer layer in thin-film solar cell technology as well as a transparent material for bifacial solar cells [8].…”
Section: Introductionmentioning
confidence: 99%
“…ZTO exhibits environmental nontoxicity, high thermal stability, wide bandgap, high transmittance, controllable electrical performances, and high electron mobility (10À15 cm 2 V À1 S À1 ). [31,32] Sha et al reported the PCE of 17.21% for mesoporous ZTO layerbased PSCs. [33] Wu et al fabricated PSCs by applying ZTO as ETL with a PCE of 16.0%, which is much lower than the best PCE reported so far.…”
Section: Introductionmentioning
confidence: 99%
“…As a multifunctional n‐type semiconductor, ZTO is another promising metal oxide with excellent optical and electronic properties, which has been widely used in many fields, such as transistors, solar cells, and Li‐ion batteries. ZTO exhibits environmental nontoxicity, high thermal stability, wide bandgap, high transmittance, controllable electrical performances, and high electron mobility (10−15 cm 2 V −1 S −1 ) . Sha et al reported the PCE of 17.21% for mesoporous ZTO layer‐based PSCs .…”
Section: Introductionmentioning
confidence: 99%